Cinquenta anos do Mini Cooper: uma viagem pelo tempo por meio da Ilustração - Pizarro, Carolina Vaitiekunas; Nakata, Milton Koji [UNESP] (My University, 2014)
The use of images as a mean of human knowledge transmission dates from the earliest records of visual communication with the cave paintings. Throughout history, the communicating function remained and was extended for a variety of approaches, including illustration, which plays an important role by transmitting a content to be communicated on a creative and unique way. The advertising area relies largely on the communicative power of illustration, using it as a visual aid on different ways and medias. The advertising pieces aimed at the automotive sector – especially those developed by BMW for the Mini Cooper model – broadly employs illustrations to spread the word about the product and its attributes, seeking to communicate it using an original way. With a qualitative approach to the case study, this article analyzes the illustrations produced by the South African design studio Am I Collective as part of a video prepared by South African advertising agency Blackriver FC as a celebration campaign for the fifty years of vehicle Mini Cooper, celebrated on 2009, and it aims to identify the illustrations visuals and compositions used in the construction of the covered temporal panorama.

A utilização de imagens como forma de transmissão do conhecimento humano remonta aos primeiros registros de comunicação visual com as pinturas rupestres. Ao longo da história a função de comunicar se manteve e foi ampliada para as mais diversas abordagens, entre elas a ilustração, que desempenha importante papel ao transmitir de maneira criativa e original um conteúdo a ser comunicado. A área da publicidade se vale em grande medida do poder comunicativo da ilustração, utilizando-a como recurso visual e empregando-a de diferentes maneiras e em diversos suportes. Também a publicidade voltada ao setor automotivo – em especial a desenvolvida pela BMW para o modelo Mini Cooper – emprega de maneira ampla a ilustração na divulgação do produto e seus atributos, buscando comunicá-lo de maneira original. Esse artigo analisa, a partir da abordagem qualitativa do tipo estudo de caso, as ilustrações produzidas pelo estúdio de design Sul Africano Am I Collective como parte integrante de um vídeo elaborado pela agência do mesmo país Blackriver FC , para a campanha de comemoração dos cinquenta anos do veículo Mini Cooper celebrados no ano de 2009, com o objetivo de identificar nas ilustrações os recursos visuais e composições utilizados na construção do panorama temporal abordado.
Keywords: Design; Illustration; Vehicle; Mini cooper; Design; Ilustração; Automóvel; Mini cooper